Analysis of the difference of the harmonised index of consumer prices and the national consumer price index in the Czech Republic - Vrabec, Václav; Vltavská, Kristýna; Musil, Petr; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2014)
Price indices belong to the most important topics in the economic statistics. The consumer price index and the harmonised index of consumer prices are the parts of the complex of price indices. The consumer price index belongs to the most important indicators of the price development in the Czech Republic. Relative changes of the final consumer prices of goods and services paid by inhabitants can be estimated in a representative way with the help of this index. The consumer price index for households (in total) is used for measuring inflation in the Czech Republic. The harmonised index of consumer prices is developed as the result of the need of comparable measurement of the inflation trends Member States of the European Union. The aim of this work is to find and analyse the differences between the national consumer price index and the harmonised index of consumer prices. These differences will be searched not only in the methodologies but in the final values as well. There is also shown development of the differences throughout the time. It will outline the development of the both indices in the future including their differences. This work should provide the clear and integral source of information about indices in general; the consumer price index, the harmonised index of consumer prices and their differences.
Vedoucí práce: Kristýna Vltavská
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: statistické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses